Compound maximal motor unit response is modulated by contraction intensity, but not contraction type in tibialis anterior. Issue 17 (8th September 2019) - Tallent, Jamie; Goodall, Stuart; Kidgell, Dawson J.; Durbaba, Rade; Howatson, Glyn
Abstract: Determining a single compound maximal motor response ( M MAX ) or an average superimposed M MAX response ( M SUP ) are commonly used reference values in experiments eliciting raw electromyographic, motor evoked potentials, H‐reflexes, and V‐waves. However, existing literature is limited in detailing the most appropriate method to normalize these electrophysiological measures. Due to the accessibility of assessment from a cortical and spinal perspective, the tibialis anterior is increasingly used in literature and hence investigated in this study. The aims of the present study were to examine the differences and level of agreement in M MAX / M SUP under different muscle actions and contraction intensities. Following a familiarization session, 22 males visited the laboratory on a single occasion. M MAX was recorded under 10% isometric and 25% and 100% shortening and lengthening maximal voluntary contractions (MVC) at an angular velocity of 15° sec − 1 . M SUP was also recorded during 100% shortening and lengthening with an average of five responses recorded. There were no differences in M MAX or M SUP between contraction types. All variables showed large, positive correlations ( P  < 0.001, r 2  ≥ 0.64). M MAX amplitude was larger ( P  < 0.001) at 100% shortening and lengthening intensity compared to M MAX amplitude at 10% isometric and 25% lengthening MVC. Bland‐Altman plots revealed a bias toward higher M MAX at the higher contraction intensities. Despite M SUP being significantly smaller than M MAX ( P  < 0.001) at 100% MVC, M SUP showed a large positive correlation ( P  < 0.001, r 2  ≥ 0.64) with all variables. It is our recommendation that M MAX should be recorded at specific contraction intensity but not necessarily a specific contraction type. Abstract : The study investigated the effect of contraction type and intensity on maximal compound action potential in the tibialis anterior. It is our recommendation that maximal compound action potential should be recorded at specific contraction intensity but not necessarily a specific contraction type.